Lignin Production from Oil Palm Biomass - Zamardina, Zainal (2013)
Malaysia is currently one of the world‟s top producers of oil palm products. The palm oil milling sector in Malaysia generates millions of metric tonne of oil palm waste annually. These include the empty fruit bunches (EFB) generated at the oil mill, the oil palm fronds (OPF) available throughout the year and the oil palm trunks (OPT) which are generated at felling. Depending on the type of residue, it is mulched, burned as fuel or burned in the fields. It makes the good reasons to fully exploit the potential use of this waste. The lignin can be used as high value-added product. This research is to extract lignin from oil palm biomass. Lignin is the most difficult component of biomass to be degraded due to its complex structure, high molecular and high insolubility. The solvent extraction method is used in this research. Various differences of the sodium hydroxide concentration are used as main parameter in this research. As the results, the different amount of lignin produced from oil palm biomass by using different concentrations of sodium hydroxide. The total yields of 5% NaOH, 10% NaOH and 20% NaOH soluble lignin from oil palm trunk and frond are 4.46% and 4.44% respectively.